2017
DOI: 10.5376/ijh.2017.07.0012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Growth Curve of Elephant Foot Yam under Extreme Stress and Plant Sensitivity

Abstract: Plant sensitivity under extreme stress in harsh agro-climatic environment for yam plants is studied to maximise yam yield for different seed weights. Longitudinal growths of 60 Elephant-foot-yam, 20 for each seed weight 500 g, 650 g and 800 g are examined in a field experiment conducted at Indian Statistical Institute Giridih, Jharkhand. Little manure and a few irrigations were available during the experiment. In order to maximise total yield, we examine yam growth under stress of interim yam detachment with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…The earlier studies reported in Dasgupta (2017a), Dasgupta (2017b) indicated that yam detachment at the time of second interim growth recording is superior. The longitudinal growth curves of yam growth from 31 plants over different seed weights, all subjected to interim yam detachment at the time of second growth recording are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The earlier studies reported in Dasgupta (2017a), Dasgupta (2017b) indicated that yam detachment at the time of second interim growth recording is superior. The longitudinal growth curves of yam growth from 31 plants over different seed weights, all subjected to interim yam detachment at the time of second growth recording are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Yam plants are found to be stress resistant when cultivated in a harsh agro-climatic environment. Seed weight 800 g is seen to be appropriate for high yield in a study reported in Dasgupta (2017a). When the stress is extreme for plant survival, higher seed weight supports the plant growth at initial stage and 800 g of seed weight produced more yam in an experiment conducted in Giridih, Jharkhand (India).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations